The effectiveness of National Energy Efficiency Action Plan (NEEAP) for attaining sustainable development in Malaysia - Aktar, Most Asikha (2023)
Due to development process and high economic growth, Malaysia has been facing serious environmental problems in terms of increased energy Carbon-dioxide-equivalents (CO2-e) emissions. Therefore, to increase energy efficiency (EE), Malaysia is now implementing the National Energy Efficiency Action Plan (NEEAP, 2016-2025) with the main objective of balancing economic and social needs with environmental priorities. However, there are still a lack of studies that analyse the economic and social impacts of NEEAP in Malaysia and measure its effectiveness in meeting environmental goals. Therefore, this study was designed to analyse the economic, social, and environmental impacts of NEEAP in Malaysia, with special attention to the Rebound Effect (RE). In achieving the results of the objectives, the study built a mixed-unit integrated Extended-Environmental Energy-Emissions Input- Output (EEEE-IO) model by modifying traditional Malaysia’s 2015 IO table (monetary transaction), incorporating MySEEA-PSUT Energy Malaysia 2015 statistics (physical transaction), and incorporating IPCC 2006 guidelines (physical transaction). So far, the study has used this integrated model with a re-spending model to analyse the NEEAP impacts under two EE scenarios other than business-as-usual, namely, the “Investment Path” and “Energy Savings Path” scenarios. The results of the study indicate that NEEAP in Malaysia had positive economic effects in the form of increased economic output and GDP, as well as social effects in the form of increased employment, with a reduction in energy CO2-e emissions defined as an environmental effect. Furthermore, the estimated RE showed that only 88 percent of the goal for reducing energy CO2-e emissions could be met. The findings' main policy implication is that the NEEAP in Malaysia will continue to be an encouraging sustainable development policy, while great care needs to be taken to achieve the government-set target when re-spending additional income from energy savings.